2007
DOI: 10.1016/j.earlhumdev.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Are prenatal psychological or physical stressors associated with suboptimal outcomes in neonates born to adolescent mothers?

Abstract: Examined whether prenatal psychological stress and/or physical stress were associated with suboptimal neonatal outcomes in a pilot study of adolescent mothers (n = 20). The results provide preliminary support for associations between prenatal psychological stress and little evidence for the association between prenatal physical stress and suboptimal neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Still, some subtle differences between our groups did exist. Specifically, consistent with prior studies finding that young mothers are at increased risk for prenatal and postpartum depression (Keenan et al, 2007;see Huang et al, 2014), in this study, pregnant clients experienced marginally more depression than those in the control group. While it is impossible to know from the design of our study if increased symptoms of depression predated the pregnancy or tended to be a consequence of it, the fact that pregnant clients experienced more depression than their matched cases in the control group suggests that there was something specific about these young mothers' pregnancy experience that added to their risk of prenatal depression.…”
Section: Client Experiencesupporting
confidence: 91%
“…Still, some subtle differences between our groups did exist. Specifically, consistent with prior studies finding that young mothers are at increased risk for prenatal and postpartum depression (Keenan et al, 2007;see Huang et al, 2014), in this study, pregnant clients experienced marginally more depression than those in the control group. While it is impossible to know from the design of our study if increased symptoms of depression predated the pregnancy or tended to be a consequence of it, the fact that pregnant clients experienced more depression than their matched cases in the control group suggests that there was something specific about these young mothers' pregnancy experience that added to their risk of prenatal depression.…”
Section: Client Experiencesupporting
confidence: 91%
“…First, it is one of the most often studied results in connection with prenatal stress and, therefore, better suited for meta-analysis (Beijers et al, 2014;Christian, 2012;Khashan et al, 2014). Second, birth weight and gestational age constitute primary birth indicators of the child's developmental health and are related to postnatal factors that are a part of the infant's postnatal experience, such as the quality of mother-infant interaction (Bernier et al, 2010;Keenan et al, 2007). Third, these birth outcomes have also been directly associated with social, emotional and cognitive dimensions of human development (Hack et al, 1991;Hoy, Bill, & Sykes, 1988;Indredavik et al, 2004;Richards, Hardy, Kuh, & Wadsworth, 2001;Wolke, 1998) underlining their value as early markers of development.…”
Section: Birth Weight and Gestational Age As Outcomementioning
confidence: 99%
“…Second, several authors have documented that high biological or psychosocial risk contexts may be characterized by greater levels of stress (Santiago, Wadsworth, & Stump, 2011). Samples that are at greater risk psychosocially may be exposed to more neighbourhood and family conflict and/or violence, in addition to the medical difficulties alluded to above (Jesse et al, 2003;Keenan et al, 2007;McCool et al, 1994). It is possible that in low-risk circumstances, the normative stressors of everyday life are not related to birth outcome, but that the relation emerges in more stressful circumstances, as may be experienced in high-risk contexts.…”
Section: National Context and Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found no significant relationship between maternal anxiety and neonatal psychological health after birth ( r =-0.115; p = 0.231), or neonatal psychological health scores including Apgar score, and birth weight. Keenan et al also reported that birth weight and Apgar score were not related to maternal anxiety and depression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%